(untitled) (Homoeopathy for All, 2025)
The term “Piles” has originated from the Latin word “pila”, meaning “a ball”. Clinically termed as Hemorrhoids, it refers to a condition which involves the formation of swollen, enlarged veins in the anus and the lower rectum. Although the presence of hemorrhoidal veins in the anal canal is a normal anatomical feature, they are referred to as Piles when they become inflamed, leading to pain, discomfort, itching or bleeding. There are different types of Piles namely external (beneath the skin around the anus), internal (within the rectum), prolapsed (protruding outside the anus) and thrombosed (containing a blood clot within an external hemorrhoid).